A Demographic profile and clinical characteristics of patients with age related hearing loss - Dofi Pebriadi; Ashadi Prasetyo; Melysa Fitriana (PERHATI-KL, 2026)
Background: Age-Related Hearing Loss (ARHL), or presbycusis, is a progressive, bilateral sensorineural hearing loss associated with the aging process. It commonly occurs in individuals over 60 years of age and is often linked to metabolic and cardiovascular disorders. Oxidative stress is a key mechanism contributing to cochlear hair cell damage, thinning of the stria vascularis, and neuronal degeneration. Although ARHL is irreversible, controlling risk factors may help slow its progression. Purpose: To determine the demographic profile, clinical characteristics, and the relationship between comorbidities and types of ARHL in patients at Sardjito Hospital, Yogyakarta. Method: This retrospective descriptive study used secondary data from the Neurotology Clinic, Department of Otorhinolaryngology– Head and Neck Surgery, Sardjito Hospital, collected from January 2022 to December 2024. A total of 120 patients diagnosed with ARHL were collected. Bivariate analysis was performed using the Chi- Square test and Fisher’s Exact Test. Result: Among 120 respondents, most were male (57.5%) and aged 60–74 years (73.3%). The most common chief complaint was hearing loss (72.5%), followed by tinnitus (20.8%) and vertigo (6.7%). Audiogram findings showed that strial presbycusis was the most prevalent type (42.5%), followed by sensory (27.5%), neural (21.7%), and cochlear (8.3%) types. Most patients had moderate hearing loss (49.2%). Cardiovascular comorbidities were present in 51.7% of patients. A significant association was found between cardiovascular comorbidities and ARHL type (p < 0.05). Conclusion: Strial presbycusis was the most common type of ARHL, and had a correlation with cardiovascular comorbidities